Epitope-based vaccine of a Brucella abortus putative small RNA target induces protection and less tissue damage in mice - Oliveira, Karen Cristina (2021)
Brucella abortusis a Gram-negative intracellular bacterium that causes a zoonotic disease called brucellosis. Although currently available vaccines for animal immunization have immunogenic potential, they still have many disadvantages, causing large-scale abortions in pregnant females and undulating fever in humans. In this context, the recent trend in the design of new vaccines against brucellosis has been based on the strategy of prediction of immunogenic epitopes selected by reverse vaccinology. Therefore, this study aimed to identify and evaluate the immunogenicity of a target vaccine epitope of putative small RNAs of B. abortus upon infection of this bacterium in a murine model. It was demonstrated in this work that small RNAs of B. abortus are expressed during the early infection of bone marrow-derived macrophages (BMDMs), and an apolipoprotein N- acyltransferase (Int) was identified as the putative target of higher expression of small RNAs. Since the apolipoprotein N-acyltransferase has decreased expression in a model of infected BMDMs, an epitope of this protein was rationally selected by immunoinformatics and explored as a candidate for vaccination against brucellosis. C57BL/6 mice immunized and challenged with B. abortus showed lower recovery in the number of viable bacteria in the liver, spleen, and axillary lymph node when compared to non-vaccinated mice. The vaccinated and infected mice showed an increase in the expression of TNF-α, IFN-γ, and IL-6, followed by an increase in the expression of the anti-inflammatory genes IL-10 and TGF-β in the liver, justifying the reduction in number and size of the observed granulomas. BMDMs stimulated with supernatant from splenocytes from vaccinated and infected mice showed more intense CD86+ marking than the other stimuli, in addition to expressing a greater amount of iNOS and consequent increase in NO production, suggesting an increase in the phagocytic and microbicidal capacity of these cells to eliminate the bacteria. Together, the results demonstrated that the vaccine peptide was able to stimulate a protective immune response in infected organisms with characteristics suggestive of a predominance of the Th1 profile.